OP0274 Cryoglobulinemic Vasculitis and Primary sjögren's Syndrome are Independent Risk Factors for Lymphoma in a Large Worldwide Population of Patients with Positive Serum Cryoglobulins. (9th June 2015) - Quartuccio, L.; Corazza, L.; Ramos-Casals, M.; Retamozo, S.; Ragab, G.M.; Ferraccioli, G.; Gremese, E.; Tzioufas, A.; Voulgarelis, M.; Vassilopoulos, D.; Koutsianas, C.; Scarpato, S.; et al.
Abstract : Background: Serum cryoglobulins (SC) may be found in many diseases (1), and the presence of serum cryoglobulins is a known risk factor for lymphoma evolution in some non malignant diseases. Objectives: The aim of this study was to distiguish the role of cryoglobulinemic vasculitis (CV), classified according to the recent validated criteria (1, 2), and primary Sjögren's syndrome (pSS) as risk factors of lymphoma in patients positive serum cryoglobulins. Importantly, SC, CV and pSS may occur together. Methods: 950 charts from consecutive patients with positive SC were evaluated. Patients carrying both pSS and HCV infection, as well as incomplete charts, were excluded. Results: 657 patients with SC were selected, 374 with CV and 283 without CV, according to the published criteria (2, 3). PSS, classified according to the American-European Group Criteria was present in 96 patients (44 with CV, 52 without). Lymphoma was reported in 61/657 (9.8%) patients with SC. Among them, CV was present in 44/61 (72, 1%; 14 also with pSS), and pSS in 17/61 (27, 9%; and 14/17 had CV). Patients with SC with CV showed an higher prevalence of lymphoma than patients with SC without CV (44/374, 11.5% vs.17/283, 6.3%; p=0.025, OR=1.93 [95%IC: 1.08-3.39]. Patients with pSS, SC and CV also showed a higher prevalence of lymphoma than patients with pSS, SC but without CV (14/44, 31.8% vs. 3/52, 7.4%; p=0.001, OR=7.62 [95%CI 2.02-28.74]. CV and pSS were confirmed as independent risk factor for lymphoma by multivariate analysis (OR 2, 18 95%CI 1, 18-3, 83, p=0, 012; OR 2, 65 95%CI 1, 04-6, 76, p=0, 042, respectively). Infection by the hepatitis C virus (HCV) was detected in 467/561 (83, 2%) patients with SC without pSS, and did not statistically predispose to lymphoma when associated with CV in this subset (p=1, 0). Conclusions: Cryoglobulinemic vasculitis and pSS are independent risk factors for lymphoma in patients with evidence of SC. Patients with both the conditions (CV and pSS) have the highest risk. In the follow-up of SC positive patients, a very high attention should be deserved to pSS, in particular when CV is present. References: De Vita S, et al. Ann Rheum Dis. 2011; 2) Quartuccio L, et al. Rheumatology (Oxford). 2014 Disclosure of Interest: None declared